Eustachian valve endocarditis: a case report on an under diagnosed entity. Issue 2 (3rd March 2020) - Hasan, Syed; Blanco, Anamarys; Faluk, Mohammed; Nasser, Hesham
ABSTRACT: Patients presenting with bacteremia and the presence of multiple infected emboli sites should be promptly investigated for heart valve endocarditis as the possible culprit. We present a case of Eustachian valve endocarditis secondary to multiple abdominal surgeries to highlight not only the importance of recognizing risks factors, other than intravenous drug use, in the pathogenesis of right sided endocarditis, but also to illustrate the significance of systematically interrogating all the heart valves, including the Eustachian valve during echocardiography.